Mesencephalic astrocyte-derived neurotrophic factor restores blood-brain barrier integrity of aged mice after ischaemic stroke/reperfusion through anti-inflammation via TLR4/MyD88/NF-κB pathway - Han, Dan; Li, Fengyang; Zhang, Haixia; Ji, Cheng; Shu, Qing; Wang, Cheng; Ni, Huanyu; Zhu, Yun; Wang, Siliang (Journal of drug targeting, 2022)
Ischaemic stroke remains a leading cause of disability and mortality worldwide and ageing-associated inflammation for the aged patients specifically leads to worse post-stroke blood-brain barrier (BBB) disruption than young subjects. Accordingly, suppression of excessive inflammation can alleviate BBB injury, which provides potential therapeutic treatment for ischaemic stroke of the aged. Prior studies revealed that mesencephalic astrocyte-derived neurotrophic factor (MANF) regulated inflammatory response and alleviated liver injury in ageing. However, it is unclear whether MANF confer similar benefit to BBB of aged mice suffered from ischaemic stroke. Transient cerebral ischaemia induced by middle cerebral artery occlusion (MCAO) was conducted in aged mice (18-20 months old). MANF was injected into the right lateral ventricle 2 h after MCAO. BBB integrity, tight junctional proteins, ultrastructure of microvessels, infarct volume, neurological scores, brain water content, pro-inflammatory cytokines and neutrophil infiltration rate were determined 72 h after MCAO. H 2 O 2 -induced senescent bEnd.3 cells were applied in the in vitro study to investigate the possible mechanism. First, we confirmed that ischaemic stroke/reperfusion in senescent condition promoted the over-expression of MANF on brain endothelial cells. Then, MANF supplement could suppress the pro-inflammatory factor production, restore BBB integrity and then alleviate infarct volume, neurological scores, brain water content and neutrophil infiltration rate. In addition, MANF maintained BBB integrity after ischaemic stroke of aged condition dependent on TLR4/MyD88/NF-κB pathway via intervention of pro-inflammatory factors production. In summary, the recognition of MANF in the process of BBB breakdown at aged condition may offer novel therapeutic approaches for ischaemic stroke.